Cladogram misreading of undergraduate students in understanding evolutionary - Sa'diatul Fuadiyah; Topik Hidayat; Didik Priyandoko (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
The student's ability to understand evolutionary studies is determined by representing a phylogenetic tree or cladogram. This study aims to determine the tree thinking ability, especially the students' reading ability in interpreting the cladogram. This descriptive study involved 29 students as subjects. Students are selected by purposive random sampling, only students who have attended and studied evolution courses. The data collection instrument used tests and interview guidelines. The test questions consist of 20 multiple choice questions with five answer choices. The difficulty level of the questions used includes understanding, applying, analyzing, and evaluating. The phylogenetic tree interpretation refers to four indicators, including the most recent common ancestor (MRCA), monophyletic group, branch proximity, contemporary descendant, and counting the branch or nodes position. The data obtained were analyzed using Microsoft Excel 2013 and Anates-V4, then presented in percentage form. The results showed that many students misinterpreted the cladogram. Furthermore, errors in cladogram interpretation occurred in monophyletic group indicators (38%), most common ancestor (59%), branch proximity (41%), contemporary ancestry (39%), and branch position calculations (53%). These results indicate that misreading of analysis in cladogram interpretation is moderate to high, so it is necessary to formulate the most appropriate way to teach phylogenetic studies in evolution.